Pfannenstiel incision for surgical excision of a huge pelvi-abdominal cystadenoma: a case report - Abdelazim, Ibrahim; AbuFaza, Mohannad (Menopause Review/Przegląd Menopauzalny, 2021)
A 56-year-old post-menopausal woman, with 3 previous caesarean sections (CSs), presented to the emergency department with abdominal distension, without abdominal pain, tenderness, and/or rigidity. The abdominal examination of the studied woman showed a mobile, pelvi-abdominal mass 4 fingers breadth above the umbilicus. Magnetic resonance imaging study of the mass showed a large, well-defined, multi-locular cystic mass measuring 25.5 x 21 cm, which was most probably a right ovarian cystadenoma. The studied woman signed a written consent form for total abdominal hysterectomy and bilateral salpingo-oophorectomy, after the normal tumour markers, and pre-operative investigations. Under general anaesthesia, an elliptical Pfannenstiel skin incision was done to remove the old CSs scars, followed by opening of the patient’s anterior abdominal wall in layers. Total abdominal hysterectomy and unilateral left SO were done first, to deliver the ovarian mass easily and intact outside the abdomen after the uterus. Due to failure to deliver the mass outside the abdomen after removal of the uterus, the right infundibulopelvic ligament was ligated behind the mass, while the mass was still inside the abdomen. A longitudinal midline incision in the upper flap of the rectus sheath (not involving the skin) was added to deliver the excised right ovarian mass outside the abdomen. Successfully, the right ovarian mass delivered intact outside the abdomen after the added longitudinal midline incision. This report highlights that the midline vertical incision is not the standard abdominal incision. Moreover, the transverse Pfannenstiel incision is cosmetically better, and should be routinely used to avoid unnecessary vertical abdominal incision.